2011
DOI: 10.1007/s00428-011-1110-1
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral lymphocyte density in serous ovarian carcinoma is superior to ERCC1 expression for predicting response to platinum-based therapy

Abstract: Intratumoral immune cells and ERCC1 expression are likely to play a role in the response of ovarian carcinoma to chemotherapy, but their impact on therapy outcome is still unclear. Therefore, 41 cases of optimally resected high grade serous ovarian carcinomas were examined retrospectively for stromal and intraepithelial lymphocyte populations and ERCC1 status in relation to response to platinum-based therapy. Based on RECIST criteria, 27 patients were classified as responsive and 14 as therapy resistant, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The first reported observation [35] found that CD3 + T cells were associated with better survial and disease-free-progression in a cohort containing several subtypes of EOC. While some studies confirmed the relation between intratumoral CD3+T cells density and EOC patient prognosis [36], [37], [38], others did not [39], [40] [31], [37], [41]. Together, these observations suggest that complex regulatory factors govern tumoral microenvironement and immune function.…”
Section: Discussionmentioning
confidence: 95%
“…The first reported observation [35] found that CD3 + T cells were associated with better survial and disease-free-progression in a cohort containing several subtypes of EOC. While some studies confirmed the relation between intratumoral CD3+T cells density and EOC patient prognosis [36], [37], [38], others did not [39], [40] [31], [37], [41]. Together, these observations suggest that complex regulatory factors govern tumoral microenvironement and immune function.…”
Section: Discussionmentioning
confidence: 95%
“…3). The race of the subjects in the studies from Steffensen et al [17, 20], Bösmüller et al [19], and Moxley et al [10] was Caucasian; whereas the race of the subjects in the studies from Sokbom K et al [18], Qi B et al [11], and Yang et al [21] was Asian. Furthermore, the same ethnicity (Chinese, studied by Qi B et al [11] and Yang Shuying et al [21]) or the same author (Steffensen et al [17, 20]) showed different outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the studies of Caucasian population show conflicting results. For example, Steffensen [20] and Bösmüller [19] indicated that the OR was greater than 1, whereas, Smith [16], Steffensen [17] and Moxley [10] did not show significant difference. Moreover, even the same author, Steffensen K.D., had conflicting results in 2011 [20] and 2008 [17].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, higher TIL infiltration has been reported to correlate with better prognosis in many tumor types, [11][12][13][14][15] including ovarian cancer for which a high degree of intratumoral CD8 C T cell was correlated with better clinical response to platinum agents. 16 However, in some cases they may protect cancer cells from the host immune system. The presence of a higher number of regulatory T cells, which suppress tumorÀspecific T cell immunity, was shown to be correlated with poor prognosis in ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%